The Interaction of Cultural Genes and the Transformation of “Collectivism” in China - Lhapeerakul, Pornpawis (Thai Journal of East Asian Studies, 2019)
the East. Within the realm of contemporary political philosophy research, there are attempts to compare the social characteristics of Individualism and Collectivism through the theory of history and social development. The West pays great attention to individual independence, freedom and personal benefits. Whereas in Asia, China represents a group-based society. Among the main reasons, there is the influence of socialism derived by Marxist ideology, and the focus that Confucian philosophy pays on communities and people in society. Nowadays, the rapid development in social, political, economic and technological spheres, has influenced the interaction of cultural genes and changed the Western concept of Individualism and the Eastern, Chinese-based concept of Collectivism.